Found in translation: a psycholinguistic investigation of idiom processing in native and non-native speakers - Carrol, G. (2015)
Idioms, as highly familiar word combinations, are processed quickly by native speakers, but are problematic for non-native speakers even at high levels of proficiency. In this thesis I explore the representation of idioms in the monolingual and bilingual lexicons. In a series of studies I investigate how native and non-native speakers of English process English idioms and idioms translated from another language. In Study 1 I used a lexical decision task to test how much an expected word is primed following the first part of an idiom, e.g. on the edge of your… seat. English native speakers and Chinese-English bilinguals were tested using English idioms and translations of Chinese idioms (e.g. draw a snake and add… feet). In Study 2 I presented the same materials in short passages to allow for more natural presentation and used eye-tracking to investigate the reading patterns for all items. I also compared figurative and literal uses of the same items to see how easily non-native speakers were able to process non-compositional meaning in the L2. In Study 3 I used the same methodology (eye-tracking of idioms used in short sentence contexts) with a higher proficiency group (Swedish-English bilinguals), with much shorter, less predictable idioms (e.g. break the ice/bryta isen) and included a set of idioms that exist in both L1 and L2. All three studies point to the same conclusion: that even in an unfamiliar translated form, the expected lexical combination was facilitated (idioms showed faster processing than control phrases), but only the highest proficiency participants also showed evidence that they were able to process the figurative meanings without disruption. Congruent items show no additional advantage, hence it is clearly L1 knowledge of what words ‘go together’ that drives the effect in translation.